(untitled) (Indian Internet Journal of Forensic Medicine and Toxicology, 2018)
Identification of an individual is very important in criminal cases like assault, murder, rape, disputed paternity and impersonation, and in civil cases like marriage inheritance and disputed sex. Estimation of stature from extremities and their parts play an important role in identifying the dead body in forensic examinations. The aim of this study was to find the correlation between foot anthropometry and stature of an individual and to derive regression formula to estimate the stature from foot anthropometry in the Central India population. This cross-sectional study was carried out on 250 deceased males of age 21 years and above brought for post-mortem examination in mortuary of Forensic Medicine Department, M.G.M. Medical College and M.Y. Hospital, Indore (MP).The mean right foot length and left foot length was 23.58±1.86 cm and 24.55±16.44 cm, respectively, whereas mean stature was found to be 163.39±5.26 cm. Mean foot breadth for both right and left foot was found to be 8.14±0.52 cm. In this study, maximum stature in males was found to be 179.5 cm, whereas minimum stature was found to be 153.1 cm. The correlation between foot length and stature was found to be to be better predictor of stature than foot breadth. As the first step in forensic analysis is establishing the identity of the person in question, where stature remains one of the primary characteristics for identification. So the findings of this study is useful for forensic experts and anthropologists.